2012
DOI: 10.1002/stem.1123
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Integration Capacity of Embryonic Stem Cell-Derived Photoreceptor Precursors

Abstract: Retinal degeneration is a leading cause of irreversible blindness in the developed world. Differentiation of retinal cells, including photoreceptors, from both mouse and human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), potentially provide a renewable source of cells for retinal transplantation. Previously, we have shown both the functional integration of transplanted rod photoreceptor precursors, isolated from the postnatal retina, in the adult murine retina, and photoreceptor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 42 publications
2
116
0
Order By: Relevance
“…The capacity to migrate may thus be restricted even within the postmitotic precursor population. Defining whether such a window exists is of crucial importance for improving transplantation efficiency, for the identification of accurate cellsurface markers [8,10], and for the isolation of a homogeneous population of integration-competent donor cells from the otherwise heterogeneous populations that arise from stem cell differentiation protocols [11,13,16,58]. Here we found that cells that migrate into the recipient retina are universally rod a-transducin -ve , despite the presence of rod a-transducin + ve cells in the subretinal space for at least 6 weeks posttransplantation (indicating that survival of more mature cells is not an issue).…”
Section: Maturation Of Donor Cells and Onset Of Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity to migrate may thus be restricted even within the postmitotic precursor population. Defining whether such a window exists is of crucial importance for improving transplantation efficiency, for the identification of accurate cellsurface markers [8,10], and for the isolation of a homogeneous population of integration-competent donor cells from the otherwise heterogeneous populations that arise from stem cell differentiation protocols [11,13,16,58]. Here we found that cells that migrate into the recipient retina are universally rod a-transducin -ve , despite the presence of rod a-transducin + ve cells in the subretinal space for at least 6 weeks posttransplantation (indicating that survival of more mature cells is not an issue).…”
Section: Maturation Of Donor Cells and Onset Of Functionmentioning
confidence: 99%
“…These findings have renewed interest in the potential to generate new photoreceptor precursors from stem cell sources [11][12][13]. Ground-breaking studies that utilize 3D culture systems have shown that embryonic stem cells (ESCs) self-organize and mimic the morphological development of the retina [14,15].…”
mentioning
confidence: 99%
“…This has been determined by comparing different protocols for mESC retinal differentiation. Some of the expression levels of photoreceptor markers are lower in adherent two-dimensional (2D) differentiation cultures compared to adult retinas 113,114 ; even though 60% of mESC-derived cells expressed CRX, these cells did not show any mature integrated photoreceptors after transplantation, 114 suggesting they were not transplantation competent. The development of the new generation of 3D retinal differentiation protocols that mimic embryonic morphogenesis of the optic vesicle 52,115 has provided the opportunity to test the importance of developmental stage to enhance transplantation competency.…”
Section: Generating Transplantation-competent Photoreceptors: Lessonsmentioning
confidence: 99%
“…52 Importantly, rod photoreceptor precursors obtained from mESC with this protocol were able to integrate and mature in the adult degenerate retina, 116,117 contrary to what had been observed with a 2D retinal differentiation protocol. 114 Using this new advanced 3D protocol, derived rod precursors transplanted in a degenerate adult retina successfully formed inner and outer segments, which were correctly orientated toward the RPE of the host retina. 116 Transplanted cells also formed synapses and were functionally active.…”
Section: Generating Transplantation-competent Photoreceptors: Lessonsmentioning
confidence: 99%
See 1 more Smart Citation